Genotypic and phylogenetic diversity of new isolates of terrestrial Xanthophyceae (Stramenopiles) from maritime sandy habitats. Issue 6 (1st November 2020) - Rybalka, Nataliya; Mikhailyuk, Tatiana; Darienko, Tatyana; Dultz, Stefan; Blanke, Matthias; Friedl, Thomas
ABSTRACT: Xanthophyceae (Stramenopiles) are common microalgae in soil habitats, but not commonly known from maritime sandy habitats. Here we studied the genetic diversity of nine new isolates of Xanthophyceae from coastal habitats using two chloroplast-encoded markers. The isolates exhibited only three morphotypes. The sequence comparisons uncovered a respectable phylogenetic diversity, including novel infraspecific genotypes, among the isolates. The phylogenetic analyses of full rbc L gene sequences identified eight of the isolates to five named species based on monophyletic origins and short genetic distances with defined taxonomic reference strains. One strain, representing a coccoid species, was within a so far unrecognised lineage of Xanthophyceae. In four clades of the rbc L phylogeny, the coastal isolates were most closely related to strains from Antarctic soil habitats. Comparisons of the psb A/ rbc L spacer region sequences, a highly variable molecular marker, uncovered a fine-scale structuring within a species which was consistent with habitat preferences. The new maritime isolates exhibited genotypes distinct from those of the same species from other habitats. It suggests that the environment selects for specific genotypes in these pioneering algae.